Fracture failure analysis and research on special taper thread of cardan shaft Shell of PDM. (April 2018) - Liu, Yang; Lian, Zhanghua; Qian, Liqin; Xia, Chengyu; Zhang, Jie; Tu, Yiliu
Abstract: The secondary crack is located near the main crack as per the macro examination and micro analysis on the fracture of a PDM (Positive Displacement Motor) shell with special taper thread, and serious defects are produced at the bottom of thread surface in the process of main crack fracture. Scanning electron microscopy observation indicates that the shear fracture point is positioned at shear fracture zone and convex of thread bottom tearing crack of sample 1#. Based on field data and type design of special thread, the matching model of special taper thread of cardan shaft shell is established in this paper, and numerical simulation of threaded connection is carried out under three different borehole curvatures. Results indicate that stress and displacement of thread increase with the borehole curvature. When the curvature reaches 30°/30 m, the maximum Von Mises stress is 967.8 MPa, which is close to the yield stress of thread material. The maximum stress occurs at the bottom of the first tooth according to the actual fracture location. Comprehensive analysis reveals that the effect of bending load occurs many times at the bottom of well. Moreover, thread surface defects result in large stress of thread, and form the weakest micro cracks at the bottom of thread. In addition, the crack occurs in the smooth area, and then rapidly extends to the shear lip, which leads to failure and even fracture of threaded connection of shell. Highlights: Did the research of macro examination about crack of thread of shell. The area had a certain brittleness through electron microscope of sample. Carried out the three-dimension simulation of thread. The largest stress was at the regions that corresponding to the actual fracture site. The effect of bending load occurs many times and defects of surface caused fracture of thread.